2020
DOI: 10.1021/acsomega.9b03451
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Lignosulfonic Acid-Grafted Polyaniline as a Hole-Transport Layer for Inverted CH3NH3PbI3Perovskite Solar Cells

Abstract: A conducting polymer of lignosulfonic acid-grafted, polyaniline-doped camphorsulfonic acid (LS-PANI-CSA), created via a low-temperature solution process, has been explored as an efficient hole-transport layer (HTL) for inverted single cation–anion CH3NH3PbI3 perovskite solar cells. The performance of the solar cell was optimized in this study by tuning the morphology and work function of LS-PANI-CSA films using dimethylsulfoxide (DMSO) as a solvent in treatment. Results showed that DMSO washing enhanced the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 96 publications
0
26
0
Order By: Relevance
“…The absolute surface WF can be estimated after the tip is calibrated with a highly oriented pyrolytic graphite (HOPG) sample. 49 As labeled in Fig. 3f, the average WF increased as the content of PFI increased in the S-P3MEET polymer.…”
Section: Optoelectronic Propertiesmentioning
confidence: 80%
See 2 more Smart Citations
“…The absolute surface WF can be estimated after the tip is calibrated with a highly oriented pyrolytic graphite (HOPG) sample. 49 As labeled in Fig. 3f, the average WF increased as the content of PFI increased in the S-P3MEET polymer.…”
Section: Optoelectronic Propertiesmentioning
confidence: 80%
“…This finding is due to the lower wettability of the mixedcation lead mixed-halide perovskite precursor solution on the fluorinated S-P3MEET substrate. 49,50 Increasing the PFI doping level in the S-P3MEET polymer more led to further reduction in grain size of the perovskite films due to the acidity of the PFI. 51,52 It has been reported that depositing perovskite onto a neutral HTL enhances the nucleation and crystallization of a perovskite active layer, with more uniform grain sizes, than depositing it onto acidic and/or basic HTL surfaces.…”
Section: Structure and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the optical bandgap of the perovskite + starch films from the Tauc plot is shown in Figure 4b. [ 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the optical bandgap of the perovskite þ starch films from the Tauc plot is shown in Figure 4b. [34] The steady-state photoluminescence (PL) and time-resolved photoluminescence (TRPL) attenuation spectra of these perovskite þ starch films are shown in Figure 4c,d, respectively. Particularly, a slight redshift of the absorption and PL were observed, which could be attributed to the different morphology of the perovskite crystal of each film sample.…”
Section: Perovskite þ Starch Film Characteristics and Solar Cell Perfmentioning
confidence: 99%